1988
DOI: 10.1002/bms.1200170112
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of moleculated radical anion abundance and calculated lowest unoccupied molecular orbital energies for polychlorinated dibenzofurans and dibenzodioxins in electron capture negative ion mass spectrometry: Evidence for negative metastable ions

Abstract: Relationships were found between experimentally measured molecular radical anion abundances and calculated lowest unoccupied molecular orbital energies (epsilon LUMO) for polychlorodibenzofurans and polychlorodibenzo-p-dioxins. Anion abundances were measured using standard mass spectrometric techniques, while epsilon LUMO were calculated by the 'Complete Neglect of Differential Overlap' method. Polychlorodibenzofurans with calculated epsilon LUMO greater than or equal to 1.6 eV show 0% molecular radical anion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…This relationship is observed for the five congeners, ranging from trichloro-to hexachlorodioxins, which show negative ion resonances within a narrow electron energy range of 0.09 eV (Table 4). Lower chlorinated dioxins yield no apparent molecular ions; those data are consistent with the known behavior of these compounds under standard ECNI-MS conditions (68).…”
Section: Environmental Compoundssupporting
confidence: 82%
See 1 more Smart Citation
“…This relationship is observed for the five congeners, ranging from trichloro-to hexachlorodioxins, which show negative ion resonances within a narrow electron energy range of 0.09 eV (Table 4). Lower chlorinated dioxins yield no apparent molecular ions; those data are consistent with the known behavior of these compounds under standard ECNI-MS conditions (68).…”
Section: Environmental Compoundssupporting
confidence: 82%
“…The electron energy required for chloride ion production decreases from 0.55 eV for dichlorodioxin to 0.22 eV for hexachlorodioxin. This pattern is consistent with a lowering of the LUMO energies for more highly chlorinated compounds (8,68). (b) Polychlorobiphenyls (PCBs).…”
Section: Environmental Compoundssupporting
confidence: 76%
“…Previously reported electron affinities for PCDDs calculated by using AM1, CNDO, and MNDO are not quantitatively reliable. Our research group has already demonstrated that the calculated structures, energies, vibrational frequencies, and ionization potentials of 2,3,7,8-TCDD agree well with the experimental values …”
Section: Introductionmentioning
confidence: 84%
“…The compu-2521,5 2526,5 The histogram (dotted line) in part a Is the theoretical fit using (M -2H)•", ( -)-, M*", and ( + H)" ion abundances from the deconvolution procedure (Figure 2). tation hardware and software has been previously described (19,20). An orbital restriction of up to 75 minimal base functions did not allow us to directly perform the calculations for the complete dimers and tetramers.…”
Section: Molecular Orbital Calculations the Published Modifiedmentioning
confidence: 99%
“…Figure 5. Experimental electron affinities versus íLUM0 calculated by MNDO method (19,20): (1) tetrafluoro-1,4-benzoquinone (24)\ (2) tetrachtoro-1,4-benzoquinone (24)(25)(26); (3) chlorine (27, 28); (4) mdinltrobenzene (26); (5) p-benzoquinone (24, 25); ( 6) hexachkxoethane (24, 29); ( 7) nitrobenzene (30, 31); (8) blacetyl (31); ( 9) naphthalene (32, 33); ( 10) chlorobenzene (34, 35); ( 11) pyridine ( 23); (12) biphenyl ( 36); ( 13) benzene ( 35); ( 14) pyrrole ( 23); (15) ethylene (24).…”
Section: £(Lumo) (Ev)mentioning
confidence: 99%